Beauty and the Tweet: How traditional media seduce in the digital age - Florent MONCOMBLE (E-REA)
Headlinese, the language of English news headlines, stands out as a unique feature of the English-speaking press worldwide. Yet, as the age of the printing press fades away in favour of digital platforms, so does the way traditional news media reach out to their readership evolve into new territories.Although originally motivated by the space constraints of the printed page, the non-standard syntactic features of headlinese have remarkably survived the shift to the web, where such constraints do not exist. Indeed, its fundamentally aoristic morphosyntax is instrumental in optimizing the relevance of headlines, thereby luring the reader into accessing content and generating revenue.However, the shift to the digital age has introduced a number of radical changes. As Internet users increasingly gather their news through Google and its ilk rather than by picking a paper at the newsstand, the importance of attractive headlines has diminished in contrast to their ability to score highly in search engines. As a result, the traditional function of headlines is being devolved to a new medium, Twitter. It is on this platform that the old headline seems to be revived, both in terms of purpose and form, but in a renewed, less aphoristic expression, which traditional media are still slow to adopt.Looking at a corpus of 1,800 news website headlines and 2,400 news tweets from some of the major online outlets provides some quantitative as well as qualitative insights into how the pragmatically oriented syntax of headlinese is evolving to keep the seduction working.